Cardiac Arrest in an Anesthesia Perspective - Andi Muhammad Nur Rahman Asiri; Iswan Wahab; Kartika Handayani (Sean Institute, 2024)
Cardiac Arrest occurs when the heart suddenly stops pumping and is the third leading cause of death in industrialized countries. Given the breadth of the medical discipline of anesthesiology, anesthesiologists always have a great opportunity to influence the safety and quality of patient care and maintain vital organ function systems during surgery. Literature searches over the last 5 years were carried out using the NCBI database, PubMed, Science Direct and the Google search engine with the keywords Cardiac Arrest, Perspective, Anesthesia. So we got 22 selected articles which were analyzed using the Unsystematic Narrative review method. Immediate treatment through providing cardiopulmonary resuscitation and eliminating causative factors is an effort to prevent death from cardiac arrest. Heart attacks regardless of location must be treated immediately. Cardiac arrest during surgery also needs to be considered because during the operation it is possible that the frequency of heart attacks associated with a significant reduction in anesthesia occurs over time. The administration of anesthesia equipment is the most common source of problems, in the ICU, it is estimated that equipment and supply problems account for 15.8% of the total side effects; similarly, equipment is involved in approximately 14–30% of all intraoperative problems. So, anesthetists are expected to always monitor and check equipment to prevent heart attacks or other complications.